The Imperative Role of Community Groups in Rural Tourism Development - Alpheaus Litheko; Marius Potgieter (African Journal of Hospitality, Tourism and Leisure, 2021)
Rural tourism, if strategically developed and managed, can make a substantial positive contribution towards the prosperity of the rural community. The management of the community group as primary stakeholders within a rural tourism development context is essential to enhance the rural collective economy of a region, augmenting the rural appearance, strengthening the rural civilisation construction, reducing the urban-rural gap, and building a cohesive and harmonious community. The primary objective is to examine the community group’s level of involvement in rural tourism development programmes; as well as to establish their level of participation in rural tourism development activities. A survey was undertaken to obtain the quantitative data needed from the community group. The findings show that the involvement of the community group in the decision-making process will assist in the effective implementation of projects without delays and contribute towards the sustainable development of rural tourism. The management of sustainable rural tourism development therefore necessitates that the needs of the community group are considered in the decision-making process and their participation therein. Participation facilitates rational cooperation, strengthens partnerships, builds trust and credibility, empowers the community group, and therefore makes management more effective.